Perinatal nicotine exposure‐induced transgenerational asthma: Effects of reexposure in F1 gestation. Issue 9 (12th July 2020) - Liu, Jie; Yu, Celia; Doherty, Terence M.; Akbari, Omid; Allard, Patrick; Rehan, Virender K.
Abstract: In a rat model, perinatal nicotine exposure results in an epigenetically driven multi‐ and trans‐generationally transmitted asthmatic phenotype that tends to wane over successive generations. However, the effect of repeat nicotine exposure during the F1 (Filial 1) gestational period on the transmitted phenotype is unknown. Using a well‐established rat model, we compared lung function, mesenchymal markers of airway reactivity, and global gonadal DNA methylation changes in F2 offspring in a sex‐specific manner following perinatal exposure to nicotine in only the F0 gestation, in both F0 and F1 (F0/F1) gestations, and in neither (control group). Both F0 only and F0/F1 exposure groups showed an asthmatic phenotype, an effect that was more pronounced in the F0/F1 exposure group, especially in males. Testicular global DNA methylation increased, while ovarian global DNA methylation decreased in the F0/F1 exposed group. Since the offspring of smokers are more likely to smoke than the offspring of nonsmokers, this sets the stage for more severe asthma if both mother and grandmother had smoked during their pregnancies. Increased gonadal DNA methylation changes following nicotine reexposure in the F1 generation suggests that epigenetic mechanisms might well underlie the transgenerational inheritance of acquired phenotypic traits in general and nicotine‐induced asthma in particular.